Preventive Efforts To Prevent Criminal Acts Of Violence Against Prisoners With Prisoners In Class II B State Detention Center Pangkalan Brandan - Saragih, Dores Ariandi; Fikri, Rahul Ardian (Best Journal of Administration and Management, 2023)
The purpose of this study is to explain the form and effect of violence against prisoners with other prisoners in the Class II B State Detention Center Pangkalan Brandan, the factors that cause violence by prisoners in the Class II B State Detention Center Pangkalan Brandan and sanctions for prisoners who commit violence between prisoners in the class II B State Detention Center Pangkalan Brandan. To obtain data in this study, research was conducted, to obtain secondary data by reading legislation, scientific works, opinions of scholars, books, articles and other materials related to this research, and field research was conducted to obtain primary data related to this research through interviews with respondents and informants in this writing. Based on the results of the research, it is known that the State Detention Center Class II B Pangkalan Brandan conducts coaching, namely independence coaching and personality coaching. Coaching, namely fostering independence and fostering personality as well as socializing human rights values in coaching and given the legal consequences given to the perpetrators of the fight itself, can be classified into two types, namely administrative sanctions, and criminal sanctions.